Development of Digital Scrapbook Module Teaching Materials as a Science Learning Innovation to Improve Students' Conceptual Understanding - Muhamad Sangaji; Fitri Damayanti; Acep Musliman; Hasbullah Hasbullah; Andri Suryana (Postgraduate, University of Mataram, 2025)
This research and development aims to produce a digital scrapbook module as an innovation in junior high school science teaching materials that is feasible, practical, and effective in improving student understanding. This research is motivated by the results of interviews with junior high school teachers in South Tangerang which showed the limitations of the use of conventional teaching materials so that learning is less interesting and not optimal. The research method used is research and development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The developed product was validated by two material experts, two media experts, and two teachers as users. The research instruments were in the form of a validation questionnaire and a questionnaire of teacher and student responses that were analyzed using a five-point Likert scale with a value range of ≤1.8 to ≥4.2. The results showed that the material feasibility obtained an average score of 4.6, media feasibility 4.4, and user response 4.6, all of which are in the very good category. Overall, the average score of expert and user assessments reached 4.5 in the very good category. These results indicate that the digital scrapbook module is not only feasible and practical to use, but also has the potential to improve the quality and effectiveness of science learning in junior high schools